Luminescence from Porous Silicon - Gupta, A.; Jain, V. K. (Defence Science Journal, 2013)
Recent observations of photoluminescene (PL) and electroluminescence (EL) from poroussilicon (PS) have prompted many theoretical and experimental studies. Bulk crystalline Si is anindirect band gap material in which .recombination is dominated by non-radiative processes.Therefore, it cannot be used as light-emitting component in Si circuits. PS is a new material formed byanodisation ofsingle crystal Si wafers in hydro fluoric (liF) solution. Luminescence from this materialis being explored for technological applications all over the world. The mechanism of luminescence isstill not well-understood. Several models have been proposed but still the facts about the strong lightemission at room temperature are unknown. This paper presents a review of the fabrication process andstudies on luminescent properties of PS. A hybrid model based on quantum confinement of carriers inthe nanometer size Si crystallites having a large number of surface states is suggested to explain theobserved properties.